The Impact of Metastatic Bone Cancers on Serum Calcium Levels: A Focused Analysis of Patient Outcomes - Muhammad Khizar Memon; Syed Uzair Mahmood; Sidra Memon; Azhar Rashid; Muhammad Ali Memon; Shahzad Ali Jiskani (Pakistan Journal of Medicine and Dentistry)
Background: Metastatic bone cancers are a significant clinical problem because metastasis disrupts normal bone homeostasis, including calcium dysregulation. Much less is known about hypocalcemia and its clinical consequences. The study analyzed serum calcium changes in metastatic bone cancer patients, assessed differences across diagnoses and clinical stages, and evaluated alkaline phosphatase levels and types of bone lesions.